Perancangan Sistem Evaluasi Kepuasan Pelanggan Perguruan Tinggi Vokasi Yang Sesuai Dengan Perkembangan Peraturan Terbaru di Politeknik ATI Padang - Verra Syahmer; Dedy Rahmad; Yafid Hafidzh (Forum Dosen Indonesia, 2022)
Universities as provides of educational service must always provide quality services to meet the needs and desires of customers. This is to get a sense of satisfaction from customers with the services that have been provided. One way to measure and determine the level of customer satisfaction is to conduct a customer satisfaction survay. Customer satisfaction surveys can be carried out using measurement instruments, one of which is a questionnaire. To be able to find out how the level of customer satisfaction with the services provided, the quesionnaire used must be in accordance with the situasion and conditions at the time of the survey. If there is a change in the service delivery process, the satisfaction measuring questionnaire must also be changed according to the changes that occur. The suitability of the satisfaction measurement questionnaire with current conditions can provide several benefits, such as the institutions being able to provide excellent service according to their needs. And the level of customer satisfaction is one aspect of accreditation so that if the questionnaire can be prepared properly, this can help the institution to improve accreditation. Keywords: Acreditation, Customer Satisfaction, Higher Education.